The Advantages of the OWA (Ordered Weighted Averaging) Method in Decision Making and Reliability Testing of Spatial Multi-Criteria Site Selection (SMCSS) Model - Saragih, Darman Ferianto; Purba, Marsedes (Faculty of Geography, Universitas Gadjah Mada, 2024)
Most SMCSS research applies a previously well-known aggregation method, namely WLC (Weighted Linear Combination), which only provides one decision-making strategy. A number of studies also do not include reliability tests of their models. This paper aims to give comprehensive descriptions of the different decision results of the OWA method and demonstrate the unique sensitivity analysis process in the model itself. A case study of the retention pond site selection in Medan City, North Sumatra Province, Indonesia, was selected for this objective. The sequence of modeling steps is parameter determination, criteria map creation, map standardization, parameter weight determination, map combination, and model validation or model sensitivity testing. Model sensitivity is tested by measuring the changes in the model's output as a result of changes in the model's inputs. The input variation of the model was arranged by applying a set number of ordered weights, which are part of the OWA method itself. Various model outputs indicate two things at once. First, the results of the SMCSS model offer a varied decision strategy, and second, the SMCSS model is proven sensitive or reliable.